Gender differences in risk-taking investment strategies in defined contribution plans - Christos Giannikos; Efstathia Korkou (Journal of Risk and Financial Management, 2022)
We study gender differences in risk-taking investment strategies in Defined Contribution (DC) Plans with the help of data from the US Federal Reserve Board's Survey of Consumer Finances (SCF). By DC plans, we refer not only to employer-sponsored plans such as 401(k)s and 403(b)s, but also to Individual Retirement Accounts (IRAs) and Roth and Keogh accounts. We suggest our own split of the SCF DC plans into risk-free and risky ones, and we build risky shares of total DC plans. We compare the risky shares of females and males in two different settings. In the first setting, we work with two samples of single people, and in the second setting we work with an extended SCF sample. In both settings, we conclude that there are no significant differences in the risky shares of total DC plans between (single) women and (single) men but that there are significant gender differences in risky IRAs and 401(k)s between (single) women and (single) men. We conclude with policy implications.
Keywords: 650; Defined Contribution Plans; financial risk-taking; gender differences; policy implications; retirement investment; single households; Survey of Consumer Finances